2017
DOI: 10.1002/jca.21611
|View full text |Cite
|
Sign up to set email alerts
|

Autograft immune effector cells and survival in autologous peripheral blood hematopoietic stem cell transplantation

Abstract: In addition to stem cells, T-cells, natural killer cells, dendritic cells, and monocytes are also collected and infused from the autograft in patients undergoing autologous peripheral blood hematopoietic stem cell transplantation. Recent reports have shown that these autograft immune effector cells can affect the clinical outcome postautologous peripheral blood hematopoietic stem cell transplantation. In this article, I will review the clinical impact on the survival of these autograft immune effector cells co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
12
1
1
Order By: Relevance
“…CD34 + CD133 + CD38 − cell content in the grafts have also been shown to affect hematologic recovery 15 . The graft natural killer (NK) cell content has been linked to early lymphocyte recovery (absolute lymphocyte count at Day 15), which has been suggested to be associated with better prognosis 16–18 …”
Section: Introductionmentioning
confidence: 99%
“…CD34 + CD133 + CD38 − cell content in the grafts have also been shown to affect hematologic recovery 15 . The graft natural killer (NK) cell content has been linked to early lymphocyte recovery (absolute lymphocyte count at Day 15), which has been suggested to be associated with better prognosis 16–18 …”
Section: Introductionmentioning
confidence: 99%
“…T-cells also show functional abnormalities for 6 months to several years. Finally, NK cell levels and functions normalise within a few weeks.Patients with early lymphoid reconstitution seem to have a more favourable prognosis than patients with late reconstitution (generally evaluated on day +15 or +30 posttransplant)[472][473][474][475]. This prognostic impact of early lymphoid reconstitution suggests that early posttransplant events are important for outcomes after autologous stem cell transplantation.…”
mentioning
confidence: 99%
“…With plerixafor-induced mobilization more immature CD34+/CD38-cells and T- and NK-cells are collected, which can lead to faster hematopoietic recovery after transplantation. 46 , 47 Few studies have shown that the grafts of MM patients had a higher number of NK-cells and CD19+ cells than those of NHL patients. However, no difference was observed in recovery.…”
Section: Use Of Plerixafor For Autologous Sctmentioning
confidence: 99%